Exploring the influence factors of digital entrepreneurship in improving the digitization of small and medium enterprises in Yemen - AL-Ghaili, Mohammed; Mahomed, Anuar Shah Bali; Yusof, Raja Nerina Raja (Scholar Publishing, 2024)
This research provides valuable insights into the impact of digital entrepreneurship on the digitalization of small and medium-sized enterprises (SMEs) in Yemen. By integrating the Technology Acceptance Model (TAM) and the Technology-Organization-Environment (TOE) framework, the research examines the role of various factors-technological, organizational, environmental, and individual, affecting technology adoption and utilization in SMEs. The study primarily explores the direct and indirect influences of these factors on actual system use, with a particular focus on the mediating roles of perceived usefulness and perceived ease of use in shaping attitudes toward technology adoption. Data were collected through a survey of 392 respondents, and the results were analyzed using partial least squares structural equation modelling (PLS-SEM). The measurement model was validated for reliability and accuracy, followed by an evaluation of the structural model to test the proposed hypotheses. The findings highlight the critical role of information and communication technology (ICT) adoption in enhancing both perceived ease of use and perceived usefulness. Additionally, the knowledge of IT entrepreneurs and government support were found to uniquely influence perceived ease of use and perceived usefulness, respectively. Both of these perceptions, in turn, positively impacted attitudes toward and the actual use of digital tools within SMEs. To address the challenges faced by Yemeni SMEs, it is recommended to enhance digitalization through ICT adoption and promote a pro-technology culture. Policymakers should create a supportive environment via targeted policies, subsidies, and public-private partnerships to foster sustainable growth and competitiveness.